The philosophy and psychology of ambivalence : being of two minds / edited by Berit Brogaard and Dimitria Electra Gatzia. - Brogaard, Berit; Gatzia, Dimitria Electra (Routledge studies in contemporary philosophy., 2021)
"This book collects original essays by top scholars that address questions about the nature, origins, and effects of ambivalence. While the nature of agency has received an enormous amount of attention, relatively little has been written about ambivalence or how it relates to topics such as agency, rationality, justification, knowledge, autonomy, self-governance, well-being, social cognition, and various other topics. Ambivalence presents unique questions related to many major philosophical debates. For example, it relates to debates about virtues, rationality, and decision-making, agency or authenticity, emotions, and social or political metacognition. It is also relevant to a variety of larger debates in philosophy and psychology, including nature vs. nature, objectivity vs. subjectivity, or nomothetic vs. idiographic. The essays in this book offer novel and wide-ranging perspectives on this emerging philosophical topic. They will be of interest to researchers and advanced students working in ethics, epistemology, philosophy of mind, philosophy of psychology, and social cognition"--